Empathic gaze: a study of human resource professionals. Issue 1 (2nd September 2021) - Lambert, Steve; Dimitriadis, Nikolaos; Venerucci, Matteo; Taylor, Mike
Abstract : Purpose: The purpose of this viewpoint paper is to explore the fixation of the eyes of human resource (HR) professionals' when identifying emotions in the context of workplace research and to propose measures that might support them in their role. Design/methodology/approach: This paper combines a contemporary literature review with reflections from practice to develop more nuanced understandings of 39 HR professionals' ability to recognise emotions. This paper used eye-tracking technology more commonly used in laboratory-based students to explore the fixation of the eye when identifying emotions. Findings: The preliminary findings suggest that HR professionals with higher levels of emotional recognition principally focus on the eyes of the recipient, whereas those with lower levels or emotional recognition focus more so the nose or the randomly across the face, depending on the level of emotional recognition. The data suggest that women are better than men, in the sample group at recognising emotions, with some variations in recognising specific emotions such as disgust. Research limitations/implications: The viewpoint paper proposes a number of implications for middle leaders and suggests that middle leaders should proactively seek out opportunities to be engaged in activities that support the Default Mode Network (DMN) function of the brain and subsequently the relationship-orientated aspects of leadership, for example, coaching other staff members. However, it has to be recognised that the sample size is small and further work is needed before any generalisations can be made. Originality/value: This paper offers a contemporary review underpinned by a preliminary study into HR professionals' ability to recognise emotions.